Thin silicon solar cells: Pathway to cost-effective and defect-tolerant cell design. (September 2017) - Augusto, André; Looney, Erin; del Cañizo, Carlos; Bowden, Stuart G.; Buonassisi, Tonio
Abstract: Thinner silicon wafers are a pathway to lower cost without compromising the efficiency of solar cells. In this work, we study the recombination mechanism for thin and thick silicon heterojunction solar cells, and we discuss the potential of using more defective material to manufacture high performance thin solar cells. Modelling the performance of silicon heterojunction solar cells indicates that at open-circuit voltage the recombination is dominated by Auger and surface, representing nearly 90% of the total recombination. At maximum power point, the surface is responsible for 50 to 80% of the overall recombination, and its contribution increases inversely with the wafer thickness. The experimental results show that for lower quality CZ material with 1 ms bulk lifetime, 60 µm-thick cells perform better than 170 µm-thick cells. The potential efficiency gain is 1% absolute. The gains in voltage of using thinner wafers are significantly higher for the lower quality CZ material, 25 mV, than for standard CZ material, 10 mV.